The flamingo - Guojing, 1983- (Random House Studio, 2022)
From a highly acclaimed illustrator comes a stunning graphic novel filled with adventure and wonder about an imaginative girl and her obsession with flamingoes. A little girl arrives, excited for a beachy vacation with her Lao Lao. The girl and her grandmother search for shells, chase crabs, and play in the sea, but when the girl finds an exquisite flamingo feather in her grandmother's living room, her vacation turns into something fantastical.